Gambaran Tekanan Darah pada Penderita Hipertensi dengan Riwayat Penggunaan Obat Antihipertensi Selama 3–5 Tahun di Wilayah Kerja Puskesmas Simpang IV Sipin Kota Jambi - MARCELINDA, WIDA TRI; Nurhusna, Nurhusna; Martawinarti, Rts Netisa; Subandi, Andi; Sari, Putri Irwanti (Jurnal Keperawatan Universitas Jambi, 2025)
Hypertension is a chronic condition characterized by a persistent increase in blood pressure that requires long-term therapy and risk factor control. This study aimed to describe the blood pressure profile of patients with hypertension who had a history of using antihypertensive medication for three to five years in the working area of Puskesmas Simpang IV Sipin, Jambi City. The study employed a quantitative descriptive design with a total sampling technique involving 40 respondents. Data were collected using a respondent characteristic questionnaire, interviews, and blood pressure measurements with a digital sphygmomanometer after participants rested for five minutes. The results showed that the majority of respondents were female (72.5%), had a college education (30%), worked as housewives (60%), and had suffered from hypertension for five years (62.5%). Based on blood pressure measurements, most respondents had systolic blood pressure in the moderate hypertension category (57.5%) and mild hypertension (42.5%). Meanwhile, diastolic blood pressure was predominantly in the mild hypertension category (62.5%), followed by high-normal (20%), normal (10%), and moderate hypertension (7.5%). The findings indicate that a portion of respondents still experienced uncontrolled blood pressure despite long-term antihypertensive medication use. Contributing factors include medication adherence, high-sodium diet, stress, and lack of physical activity. Continuous education, regular monitoring, and lifestyle modification efforts are necessary to achieve optimal blood pressure control.